Learning Strategies in Oyster Mushroom Cultivation Training in the Rohana Kudus Bungus Timur Farmers Group - Atri Bunda Sari; Setiawati Setiawati (Universitas Negeri Padang, 2019)
This research is motivated by the high participation of citizens learning in the training of Budidaya Jamur Tiram by UKM Ukhtina Suci in the Kelompok Tani Rohana Kudus Bungus Timur. Allegedly because of the learning strategy used by the instructor. This study aims to obtain information regarding: 1) learning strategies in the determination of methods by instructors, 2) learning strategies in the use of media by instructors, 3) learning strategies in patterns of interaction by instructors. This research uses a quantitative approach, a type of descriptive research. The population of this study were learning citizens who took part in training in the cultivation of Budidaya Jamur Tiram in the Kelompok Tani Rohana Kudus Bungus Timur in 2019, amounting to 15 people, all pupils were sampled called respondents. Data collection techniques using a questionnaire, data collection tools are questionnaires. The results showed that: 1) learning strategies in the determination of methods by instructors were categorized as good, 2) learning strategies in the use of media by instructors were categorized as good, 3) learning strategies in interaction patterns by instructors were categorized as good. The conclusion of this study is the use of learning strategies in the training of Budidaya Jamur Tiram is categorized very well. Suggestions in this study are expected to instructors to further improve learning strategies and to the manager is expected to provide guidance.Keywords: Strategy, Participation